Investigating the Role of the Generation Gap in the Emergence of Emerging Social Harms among Female Beneficiaries under Support in Semnan County - Heydarian, Jamshid; Sharifi, Mansour; Sharbatian, Yaqoub (Psychology of Woman Journal, 2025)
Objective: This study aims to investigate the role of the generational gap in the emergence of new social harms, with a particular emphasis on prostitution, among female beneficiaries supported by welfare institutions in Semnan County, Iran. Methods and Materials: The study employed a descriptive-survey research design using a standardized questionnaire to collect data from 260 female beneficiaries aged 20 to 29 years, selected through simple random sampling based on Cochran’s formula. The study was conducted in Semnan County during spring to autumn 2021. Validity was confirmed through expert review, and reliability was verified using Cronbach’s alpha (α = 0.89). Data analysis was conducted using SPSS version 25, employing Pearson correlation, regression analysis, and t-tests to explore the relationships among the variables: family cohesion, social isolation, depression, and the generational gap. Findings: Results indicated that the generational gap was significantly and negatively associated with family cohesion (r = -0.68, p < 0.01) and positively associated with both social isolation (r = 0.72, p < 0.01) and depression (r = 0.61, p < 0.01). Regression analysis showed that the generational gap (β = 0.17, p = 0.006), social isolation (β = 0.20, p < 0.001), and family cohesion (β = -0.28, p < 0.001) significantly predicted prostitution tendency. Depression, however, was not a significant predictor in the multivariate model (β = 0.06, p = 0.134). The model explained 19% of the variance in prostitution tendency (R² = 0.19). Conclusion: The study concludes that generational gaps and social isolation significantly contribute to increased prostitution tendency, while family cohesion serves as a protective factor. These findings underscore the need for holistic, intergenerational interventions targeting family dynamics and communication in vulnerable populations.